Anatomical features of aortic root in patients with aortic stenosis treated by TAVR: an observational study - Yang Chen; Baihua Sun; Zhongyu Wang; Moyang Wang; Hongliang Zhang; Guannan Niu; Zhenyan Zhao; Dejing Feng; Pinghai Zhang; Zhibo Jiang; Junhua Yuan; Junxian Song; et al. (BMC Medical Imaging)
Abstract Objective Transcatheter aortic valve replacement (TAVR) is a well-established technique for the treatment of aortic stenosis (AS). However, due to the complex anatomical features of the aortic root, the risk of vascular injury caused by operation under the condition of anatomical variations of the aortic root is high, and there is a lack of studies on the anatomical features of the aortic root on CT before TAVR. Therefore, this study will preliminarily summarize anatomical features of aortic root in patients with aortic stenosis treated by TAVR. Methods A retrospective study was conducted at a single center, involving 60 patients with symptomatic severe AS treated TAVR between September 2022 and December 2022. Baseline patient information, CT measurements of aortic root anatomical characteristics, and associated risks were analyzed. Results The mean age of the 60 patients was 77.72 ± 4.33 years, with 39 males (65.00%). The left ventricular ejection fraction was 65.46 ± 13.92%. Valve morphology included 38 cases (63.30%) of tricuspid valves and 22 cases (36.70%) of bicuspid valves. Common anatomical risks identified were acute aortic arch (18.33%), a short ascending aorta (10.00%, 8.33%, 16.67%, 15.00%), ascending aortic dilation (3.33%), a transverse heart (28.33%), cardiac anteversion (68.33%), a short left ventricle (5.00%), and a small left ventricle (5.00%). Conclusion Preoperative cardiac CT scans detect aortic root morphological angle abnormalities in TAVR patients. Angular dimensions of the aortic root show considerable variability among patients, which may have procedural implications for TAVR.